For readability, let c=cos(x), s=sin(x)
4cos(2x)+cos(4x) = 4c^2 - 4s^2 + s^4 + c^4 - 6s^2c^2
= (4 - 4sin^2 - 4s^2) + (s^4 + 1 - 2s^2 + s^4 - 6s^2 + 6s^4)
= (4-8s^2) + (1 - 8s^2 + 8s^4)
(3-4cos(2x)+cos(4x)) = 3 - 4 + 8s^2 + 1 - 8s^2 + 8s^4 = 8s^4
(3+4cos(2x)+cos(4x)) = 3 + 4-8s^2 + 1 - 8s^2 + 8s^4 = 8 - 16s^2 + 8s^4 = 8c^4
so, dividing, you get 8s^4/8c^4 = tan^4
You sure you copied it right? Don't see how to make it tan^6
(3-4cos(2x)+cos(4x))/(3+4cos(2x)+cos(4x))=tan^6(x)
3 answers
I tested the original equation using x = 10°
the left side was NOT equal to the right side, so the equation is not an identity.
the left side was NOT equal to the right side, so the equation is not an identity.
I confirmed the identity, the left hand side IS equal to tan^4(x), not tan^6(x).
A typo is the most likely cause.
A typo is the most likely cause.